Rediseño de planta para la producción de queso fresco y yogurt en la Asociación de Promoción Social y Desarrollo Productivo "APRODEMAG". - Chicaiza Pilataxi, Javier Orlando (2018)
The present research project has as purpose to redesign the location of areas and installation work in order to increase dairy production through the implementation of a study on the distribution of industrial plants, at the milk collection center and minimum production of cheese and yogurt ''APRODEMAG'' The proposed study is to carry out the objectives of the project that is a non-experimental research, with a field study, applying observation techniques, bibliographic review and tools such as charts, study of times and movements, design programs AutoCAD, instructional, Layouts. The results obtained it allowed to identify the critical points and deficiencies in the distribution of productive and processes areas. It was also found that initially the plant was designed for the production of bio-inputs and then it was adapted for the production of dairy products, for which its Current productivity is only 25% of the total capacity. As a proposal, it proposed a redesign of the plant distribution, applying procedures for the production process and a Layout with the appropriate location of the work areas that will help to improve the production, quality, ordering, control, hygiene and maintenance of the installations. It is concluded that the plant has several design and distribution defects so the introduction of new modifications will increase its efficiency and productivity, all this contributes significantly as a basis for the development of new projects that help to achieve the main objective of the organization that is to increase the production of fresh cheese and implement a new area for the production of yogurt in the future.